2008
DOI: 10.3860/taper.v15i2.85
|View full text |Cite
|
Sign up to set email alerts
|

Unguarded Patterns of Thinking: Physical and Topical Structure Analysis of Student Journals

Abstract: Journals have been utilized in classrooms both

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 15 publications
3
14
2
Order By: Relevance
“…Interestingly, findings of the present study resonate with the findings of some studies (Liangprayoon, Chaya, & Thep-ackraphong, 2013;Alamaden 2006;Carreon, 2006;Simpson, 2000;Schneider & Connor, 1990;Connor & Farmer, 1990) where presence or use of topical progressions is highly evident in the students' writings.…”
Section: Topical Structure Analysissupporting
confidence: 89%
“…Interestingly, findings of the present study resonate with the findings of some studies (Liangprayoon, Chaya, & Thep-ackraphong, 2013;Alamaden 2006;Carreon, 2006;Simpson, 2000;Schneider & Connor, 1990;Connor & Farmer, 1990) where presence or use of topical progressions is highly evident in the students' writings.…”
Section: Topical Structure Analysissupporting
confidence: 89%
“…The results of this study are in line with some previous studies (Barabas & Jumao-a, 2009;Carreon, 2006;Fan & Hsu, 2008;Schneider & Connor, 1990) which revealed that EFL students employed sequential progression the most in their essays. A plausible explanation for the highest number of sequential progression used is the text type or the rhetorical mode of the essay.…”
Section: Proportion Of Topical Progression In Selected Essays Of Highsupporting
confidence: 82%
“…6, No. 7;2013 At first, TSA was employed as an objective method to examine coherence and proportions of topical progression in students' texts (Almaden, 2006;Barabas & Jumao-a, 2009;Carreon, 2006;Lautamatti, 1987;Simpson, 2000;. More recently, it has been taught to students as a revision strategy to investigate their writing coherence (Cerniglia, et al, 1990;Chiu, 2004;Connor & Farmer, 1990;Fan & Hsu, 2008;Nunan, 1994;Sakontawut, 2003).…”
Section: Language and Community (1) When A Human Infant A Is Born Intmentioning
confidence: 99%
“…Contrary to examining the thematic development in students' academic writings, a study by Carreon (2006) aimed at examining the topical development of students' personal journals. Carreon used TSA in investigating cohesion in 20 journals of two ESL composition classes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Furthermore, Carreon (2006) attributed her results of employing more sequential progressions to the journal type of writing where students are familiar and fully aware of their personal content they include in their writings, unlike the unfamiliar topics of academic writing. This enabled them to explore and elaborate on the subject well, which affirmed using different sequential topics.…”
Section: Figure 8 Percentages Of the Three Types Of Progressionsmentioning
confidence: 99%